(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Transdermal drug delivery system is becoming more popular in the field of modern pharmaceutics. In the present work, an attempt has been made to develop a transdermal therapeutic system of drug Fluconazole with different concentration of hydrophilic (HPMC) and hydrophobic (ERS 100) polymeric system by solvent evaporation technique by using 30 ww of Dibutyl phthalate incorporated as plasticizer and DMSO as a penetration enhancer. The physicochemical compatibility of the drug and the polymers was studies by Fourier transform infra-red (FTIR) spectroscopy analysis shows that there is no interaction between drug, HPMC and ERS 100. All the prepared formulations were subjected to physical studies (Weight Variation, Thickness, Folding endurance, Drug content determination, Flexibility or Tensile strength, Flatness, Percentage of moisture uptake, Percentage moisture loss, and Stability studies). Based on the physicochemical and In-vitro dissolution study formulation P2 (ERSHPMC, 28) were the best formulation. The release profile of optimized formulation indicated that the permeation off the drug from the patches was showed diffusion controlled mechanism. Hence, it can be concluded that Fluconazole with the high concentration of hydrophilic polymer showed the better release.